Designing engaging interaction with contextual patterns for an educational game - Chien-Sing, Lee (2008)
This paper aims to address two problems. The first problem is how to develop engaging (deep and meaningful) pedagogical patterns and still ensure there is Sufficient incremental cognitive complexity. The second problem deals with how to connect pedagogical patterns to HCI and software engineering to form a systemic interaction design framework. An educational game is used as all example. Significance of the study lies in the development of a means to create interaction designs around design-for-engagement requirements and the flexible scaling and synergy of different frames of reference (pedagogy-application domain-HCI- software engineering) through instantiations from the synergised patterns: reducing error and cost and encouraging new experimentations with transfer of engaging learning.